Les Arméniens de Constantinople au xixe siècle. Éssai de topographie urbaine. - Taline Ter Minassian (Revue des Mondes Musulmans et de la Méditerranée)
Although demographic data may vary considerably – from 84 093 according to the Ottoman Census of 1914 to 161 000 according to the census provided by the Armenian Patriarcate in 1913-1914, Armenians are indisputably a major component of the social life of the Ottoman capital city at the turn of the 20th century. Constantinople is also the political and cultural “capital of the Armenians” of the Ottoman Empire, with 47 parishes, 42 schools and a dozen of secondary schools, among which Catholic and Protestant ones, as well as 415 newspapers (between 1839 and 1922). Constantinople is “the City” par excellence - Bolis – attracting many Armenians from Anatolia. Therefore, it is relevant to study how Armenians – established ones as well as newcomers – build their own social sphere and become the agents of a certain Westernisation of the urban and cultural landscape of the Ottoman metropolis at the very eve of their own disappearance as a community after the Armenian genocide and the collapse of the Ottoman Empire.